A comment on Campaign Contributions and Roll-Call Voting by Grier, Grier and Mkrtchian (2023) - Harry He; Tereza Petrovičová (Institute for Replication (I4R), 2023)
In their study, Grier et al. (2023) explore the causal relationship between campaign contributions and roll-call voting. Their analysis focuses on the influence of campaign contributions on two specific anti-sugar votes conducted in 2013 and 2018. The authors identify a substantial increase in inflationadjusted sugar contributions from the sugar industry to incumbent politicians between these two voting events. The aim of our research is to replicate and validate the authors' main models. In addition to cross-platform replication, we conduct several robustness checks to further examine the reliability of their findings. These include (1) clustering the standard errors, (2) utilizing an Ordinary Least Squares (OLS) model instead of the authors' logistic regression, and (3) altering the dependent variable to represent the change in the vote from 2013 to 2018. Our results largely confirm the authors' findings and reveal additional insights regarding the money buys vote hypothesis.
Keywords: 330